Ion-coated composite conductive agent, positive electrode and sulfide all-solid-state battery

By covering the conductive ion-conducting cladding layer on the conductive agent matrix of the sulfide solid-state battery, the problems of narrow electrochemical windows and short cycle life of the sulfide solid-state battery are solved, and higher lithium ion transmission flux and battery stability are achieved.

CN119833636APending Publication Date: 2025-04-15CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510036012.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The narrow electrochemical window of sulfide solid-state batteries leads to limited battery cycle life and energy density, especially when using high-energy density ternary cathode materials.

Method used

The lithium ion transport capability at the electrolyte/positive material interface is improved by covering the ion-conducting coating layer on the conductive agent matrix, including lithium ions and oxygen ions.

Benefits of technology

It effectively improves the battery cycle performance and rate performance, increases the lithium ion transmission flux, reduces the structural collapse and side reactions of the positive electrode material, and improves the stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833636A_ABST
    Figure CN119833636A_ABST
Patent Text Reader

Abstract

The invention relates to an ion-coated composite conductive agent, a positive electrode and a sulfide all-solid-state battery, the ion-coated composite conductive agent comprises a conductive agent matrix and an ion-conductive coating layer used for increasing lithium ion transmission flux, the outer wall surface of the conductive agent matrix is coated with the ion-conductive coating layer, and the ion-conductive coating layer comprises lithium ions. The conductive agent matrix is configured to increase the electron transmission capability of the composite conductive agent, and the conductive ionic coating layer coats the conductive agent matrix, so that the structure of the positive electrode material can be kept stable, and the conductive ionic coating layer contains a large amount of lithium ions, so that the conductivity of the positive electrode material is improved. A large number of lithium ions can improve the polarization influence caused by a space charge layer at an electrolyte / positive electrode material interface, improve the lithium ion transmission capability at the interface, increase the lithium ion transmission flux, and facilitate the improvement of the cycle performance and rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an ion-encapsulated composite conductive agent, a positive electrode and a sulfide all-solid-state battery. Background Art

[0002] Compared with traditional liquid batteries, solid-state batteries have the advantages of high safety, high energy density, and wide operating temperature window. Among them, sulfide solid electrolytes have high ionic conductivity (10 -3 ~10 -2 S cm -1 ) and good mechanical properties and is considered to be one of the most promising electrolyte materials for achieving high-performance all-solid-state batteries.

[0003] However, the electrochemical window of sulfide solid electrolytes is generally narrow (about 1.71-2.5V). During the battery charging and discharging process, the electrolyte is prone to undergo a series of side reactions with the positive electrode material, affecting the battery cycle life and energy density. When the positive electrode material is a ternary positive electrode material of a high energy density system, this adverse effect is more significant.

[0004] According to most literature reports, one of the reasons is that the electrons on the surface of the carbon-based conductive agent will induce the decomposition of the surrounding sulfide electrolyte. The side reaction product is an insulating layer, and the ionic conductivity at the interface is seriously reduced. The second reason is that the potential difference between the sulfide and the positive electrode active material causes lithium ions to form a space charge layer at the interface. The lithium ion concentration in the space charge layer is low, which makes lithium ion deintercalation and transmission difficult, reducing the coulombic efficiency.

[0005] Therefore, in solid-state batteries, the problem of rapid capacity decay can be effectively improved by constructing a suitable artificial interface.

[0006] For example, some related technologies use sol-gel technology to prepare oxide colloids, and coat the positive electrode materials to obtain high-capacity, high-stability composite positive electrode materials, which solves the problem of capacity attenuation of sulfide solid-state batteries during long cycles. The reason is that the surface crack defects of the positive electrode materials are reduced, the side reactions between the positive electrode and the sulfide solid electrolyte are suppressed, and the thermal instability of the interface is reduced, which is conducive to improving the comprehensive performance of sulfide solid-state batteries. However, the use of metal oxides to coat the positive electrode materials in this method will greatly reduce the ionic conductivity of the positive electrode active material / electrolyte interface, resulting in battery capacity attenuation and rate performance degradation.

[0007] For example, in other related technologies, the organic lithium salt layer coated on the surface of the electrolyte can be decomposed in situ during the battery cycle to form a stable positive electrode-sulfide electrolyte interface, which helps to improve the interface stability between the electrolyte and the positive electrode in the composite positive electrode of the solid-state battery, inhibit the electrolyte structure damage caused by chemical or electrochemical side reactions during the cycle, the decrease in ionic conductivity, the generation of harmful reaction byproducts, and other problems, effectively improve the battery capacity attenuation caused by the increase in polarization on the composite positive electrode side during the cycle, and improve the service life of the solid-state battery. However, this method of coating the interface layer on the surface of the active material in large quantities will lead to a decrease in the proportion of active materials, resulting in a loss of specific capacity of the battery. Summary of the invention

[0008] The embodiments of the present application provide an ion-coated composite conductive agent, a positive electrode and a sulfide all-solid-state battery, which can improve the polarization effect caused by the space charge layer at the electrolyte / positive electrode material interface, improve the lithium ion transmission capacity at the interface, increase the lithium ion transmission flux, and are beneficial to the improvement of the battery cycle performance and rate performance.

[0009] In a first aspect, an ion-coated composite conductive agent is provided, which includes a conductive agent matrix and an ion-conductive coating layer for increasing the lithium ion transmission flux, wherein the ion-conductive coating layer is coated on the outer wall surface of the conductive agent matrix, and the ion-conductive coating layer includes lithium ions.

[0010] In some embodiments, the ion-conducting coating layer further includes oxygen ions.

[0011] In some embodiments, the ion-conducting coating layer includes lithium niobate LiNbO3, lithium titanate Li4Ti5O 12 , lithium tantalate LiTaO3 or more.

[0012] In some embodiments, the mass ratio of the ion-conductive coating layer to the mass ratio of the ion-coated composite conductive agent is 1%-20%.

[0013] In some embodiments, the conductive agent matrix includes one or more of conductive carbon black CB, vapor grown carbon fiber VGCF, SuperPLi, conductive graphite and carbon nanotube CNT.

[0014] In a second aspect, a method for preparing the ion-encapsulated composite conductive agent as described above is provided, comprising:

[0015] The raw material of the ion-conducting coating layer and the conductive agent matrix are ball-milled to obtain a mixed powder, wherein the raw material of the ion-conducting coating layer includes a lithium source and a metal oxide;

[0016] The mixed powder is annealed to obtain an ion-coated composite conductive agent.

[0017] In some embodiments, the lithium source includes one or more of lithium carbonate Li2CO3, lithium oxide Li2O, lithium sulfate Li2SO4, lithium nitrate LiNO3 and lithium hydroxide LiOH.

[0018] In some embodiments, the metal oxide includes one or more of niobium pentoxide Nb2O5, titanium dioxide TiO2, and tantalum pentoxide Ta2O5.

[0019] In some embodiments, the molar ratio of the metal oxide in the raw material of the ion-conducting coating layer is 40%-60%.

[0020] In some embodiments, the mass fraction of the conductive agent matrix in the mixed powder is 90%-97%.

[0021] In some embodiments, the annealing treatment includes: the ambient atmosphere is oxygen, the annealing temperature is 350° C.-600° C., and the annealing time is 10-15 hours.

[0022] In a third aspect, a positive electrode is provided, which includes a ternary positive electrode material, a binder, a positive electrode current collector, and any of the ion-coated composite conductive agents described above.

[0023] In some embodiments, the ternary cathode material includes LiCoO2, Li(Ni a Co b X c )O2 or Li Mn2O4, wherein a+b+c=1, X=Mn or Al.

[0024] In some embodiments, the particle size of the ternary positive electrode material is 500nm-100μm.

[0025] In some embodiments, the binder includes one or more of polythiophene, polypyrrole, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene, polyacrylamide, and ethylene-propylene-diene copolymer resin.

[0026] In some embodiments, the positive electrode current collector includes one or more of aluminum foil, carbon-coated aluminum foil or composite aluminum foil.

[0027] In a fourth aspect, a method for preparing a positive electrode as described above is provided, comprising:

[0028] The ternary positive electrode material, the binder and a part of the ion-coated composite conductive agent are uniformly mixed and then sprayed on the surface of the positive electrode current collector to form a positive electrode film;

[0029] The remaining ion-coated composite conductive agent is coated on the surface of the positive electrode film to form a composite conductive agent layer to obtain a positive electrode.

[0030] In a fifth aspect, a sulfide all-solid-state battery is provided, which comprises a sulfide solid electrolyte, a negative electrode and a positive electrode as described above, wherein the sulfide solid electrolyte is coated on the surface of the positive electrode to form an electrolyte layer, and the negative electrode is covered on the surface of the electrolyte layer.

[0031] In some embodiments, the sulfide solid electrolyte includes LGPS, Li3PS4, Li7P3S 11 , Li6PS5C 1 or Li8PS5I.

[0032] In some embodiments, the particle size of the sulfide solid electrolyte is 1 μm-10 μm.

[0033] In some embodiments, the electrolyte layer has a thickness of 20 μm-80 μm.

[0034] In some embodiments, the ternary positive electrode material, binder, ion-coated composite conductive agent and sulfide solid electrolyte are taken as a whole. According to the mass fraction, the ternary positive electrode material accounts for 40%-80%, the binder accounts for 0%-10%, the ion-coated composite conductive agent accounts for 2%-15%, and the sulfide solid electrolyte accounts for 10%-50%.

[0035] The beneficial effects of the technical solution provided by this application include:

[0036] The embodiments of the present application provide an ion-coated composite conductive agent, a positive electrode and a sulfide all-solid-state battery. The conductive agent matrix is ​​configured to increase the electron transmission capacity of the composite conductive agent, and the ion-conductive coating layer is coated on the conductive agent matrix, which can not only maintain the stability of the positive electrode material structure, but also because the ion-conductive coating layer contains a large amount of lithium ions, a large amount of lithium ions can improve the polarization effect brought by the space charge layer at the electrolyte / positive electrode material interface, improve the lithium ion transmission capacity at the interface, increase the lithium ion transmission flux, and is beneficial to the improvement of the battery cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0038] Figure 1 A schematic diagram of an ion-encapsulated composite conductive agent provided in an embodiment of the present application;

[0039] Figure 2A flow chart for preparing the ion-coated composite conductive agent provided in the embodiments of the present application;

[0040] Figure 3 This is a battery cycle performance test diagram provided in an embodiment of the present application.

[0041] In the figure: 1. Conductive agent matrix; 2. Ion-conductive coating layer. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0043] See also Figure 1 As shown, an embodiment of the present application provides an ion-coated composite conductive agent, which includes a conductive agent matrix 1 and an ion-conductive coating layer 2 for increasing the lithium ion transmission flux, wherein the ion-conductive coating layer 2 is coated on the outer wall surface of the conductive agent matrix 1, and the ion-conductive coating layer includes lithium ions.

[0044] In the present application, the conductive agent matrix is ​​configured to increase the electron transmission capacity of the composite conductive agent, and the ion-conductive coating layer is coated on the conductive agent matrix, which can not only maintain the stability of the positive electrode material structure, but also because the ion-conductive coating layer contains a large amount of lithium ions, a large amount of lithium ions can improve the polarization effect brought by the space charge layer at the electrolyte / positive electrode material interface, improve the lithium ion transmission capacity at the interface, increase the lithium ion transmission flux, and is beneficial to the improvement of battery cycle performance and rate performance.

[0045] During the charge and discharge process of the ternary positive electrode material, the oxygen atoms will combine with the sulfur atoms in the sulfide solid electrolyte, causing the collapse of the layered structure of the ternary positive electrode material. In order to solve this problem, in the present application, the ion-conducting coating layer also includes oxygen ions. The oxygen ions provided by the ion-conducting coating layer will be freed to the vicinity of the ternary positive electrode material during the charge and discharge process, and can be replenished to the oxygen vacancies in time, ensuring the structural stability of the ternary positive electrode material and improving the cycle stability performance of the sulfide all-solid-state battery.

[0046] Further, as an example, the ion-conducting coating layer includes lithium niobate Li NbO 3, lithium titanate Li 4 Ti 5 O 12 , one or more of lithium tantalate Li TaO3.

[0047] Preferably, the ionic coating layer is lithium niobate Li NbO 3 .

[0048] Further, as an example, the mass ratio of the ion-conducting coating layer to the mass ratio of the ion-coated composite conductive agent is 1%-20%. Too low a coating content may lead to the risk of exposing the conductive agent matrix, causing direct contact between the carbon conductive agent and the sulfide electrolyte, which may aggravate the decomposition side reaction of the sulfide electrolyte.

[0049] Preferably, the mass ratio of the ion-conductive coating layer to the mass ratio of the ion-coated composite conductive agent is 3%-10%.

[0050] Compared with coating the positive electrode material or coating the electrolyte material, the use of an ion-conductive coating layer to directly coat the conductive agent matrix has a lower coating mass proportion, which is beneficial to improving the energy density of sulfide solid-state batteries.

[0051] Further, as an example, the conductive agent matrix includes one or more of conductive carbon black CB, vapor grown carbon fiber VGCF, SuperPL i, conductive graphite and carbon nanotube CNT.

[0052] Preferably, the conductive agent matrix is ​​vapor grown carbon fiber VGCF.

[0053] See also Figure 2 As shown, the present application embodiment also provides a method for preparing an ion-coated composite conductive agent, which comprises the following steps:

[0054] 101: ball-milling the raw material of the ion-conductive coating layer and the conductive agent matrix to obtain a mixed powder, wherein the raw material of the ion-conductive coating layer includes a lithium source and a metal oxide.

[0055] Specifically, step 101 can be divided into two steps. The first step is to ball-mill the lithium source and the metal oxide to mix them evenly, and the ball-milling conditions are 50-500r / min, 2-4h; the second step is to ball-mill them with the conductive agent matrix, and the ball-milling conditions are 100-200r / min, 2-4h.

[0056] 102: Annealing the mixed powder to obtain an ion-coated composite conductive agent.

[0057] In step 102, the annealing treatment includes: the ambient atmosphere is oxygen, the annealing temperature is 350℃-600℃, and the annealing time is 10-15h. The reason for choosing this annealing temperature is that too high annealing temperature may cause the crystal structure of the ion-conducting coating layer to change, affecting the ion conduction efficiency, while too low annealing temperature is not conducive to the growth of ion-conducting coating layer crystals, resulting in insufficient bonding between the ion-conducting coating layer and the conductive agent matrix; for the annealing time, generally extending the annealing time can improve the structural stability of the composite material. It should be noted that when the annealing temperature is high, only a short annealing time is required to achieve complete coating growth of the surface ion-conducting coating layer crystals. When the annealing temperature is low, a longer annealing time is required to achieve the same crystallization effect.

[0058] The high temperature annealing method is used to prepare the ion-coated composite conductive agent, which can make the ion-conducting coating layer more uniform and stable.

[0059] Further, as an example, the lithium source includes one or more of lithium carbonate Li2CO3, lithium oxide Li2O, lithium sulfate Li2SO4, lithium nitrate LiNO3 and lithium hydroxide LiOH.

[0060] Further, as an example, the metal oxide includes one or more of niobium pentoxide Nb2O5, titanium dioxide TiO2, and tantalum pentoxide Ta2O5.

[0061] Further, as an example, the molar proportion of the metal oxide in the raw material of the ion-conducting coating layer is 40%-60%.

[0062] Further, as an example, the mass fraction of the conductive agent matrix in the mixed powder is 90%-97%.

[0063] The embodiment of the present application also provides a positive electrode, which includes a ternary positive electrode material, a binder, a positive electrode current collector, and an ion-coated composite conductive agent. Since the ion-conductive coating layer contains a large amount of lithium ions, a large amount of lithium ions can improve the polarization effect caused by the space charge layer at the electrolyte / positive electrode material interface, improve the lithium ion transmission capacity at the interface, increase the lithium ion transmission flux, and is conducive to the improvement of battery cycle performance and rate performance.

[0064] Further, as an example, the ternary positive electrode material includes LiCoO2, Li(Ni a Co b X c )O2 or Li Mn2O4, wherein a+b+c=1, X=Mn or Al.

[0065] Furthermore, the smaller the material particle size, the larger the specific surface area. Considering that the conductive agent matrix is ​​the main component of the composite conductive agent, if the particle size of the ternary positive electrode material is too small, the conductive agent matrix component will account for too low a proportion; and if the particle size of the ternary positive electrode material is too large, the electrode porosity will increase, affecting the transmission of electrons on the surface of the active material particles, and the efficiency of the active material electrical performance will be reduced. Taking all factors into consideration, in this application, the particle size of the ternary positive electrode material is 500nm-100μm.

[0066] Further, as an example, the binder includes one or more of polythiophene, polypyrrole, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene, polyacrylamide, and ethylene-propylene-diene copolymer resin.

[0067] Further, as an example, the positive electrode current collector includes one or more of aluminum foil, carbon-coated aluminum foil or composite aluminum foil.

[0068] The present invention also provides a method for preparing a positive electrode, which comprises the following steps:

[0069] 201: The ternary positive electrode material, the binder and a portion of the ion-coated composite conductive agent are uniformly mixed and then sprayed on the surface of the positive electrode current collector to form a positive electrode film.

[0070] In step 201, the binder and a portion of the ion-encapsulated composite conductive agent may be pre-mixed, and then the ternary positive electrode material may be added for ball milling and mixing. The purpose of adding the ion-encapsulated composite conductive agent is to increase the conductivity of the positive electrode sheet.

[0071] 202: Coating the remaining ion-coated composite conductive agent on the surface of the positive electrode film to form a composite conductive agent layer to obtain a positive electrode.

[0072] In step 202, the ion-encapsulated composite conductive agent is coated by electrostatic spraying or gravure coating. The ion-encapsulated composite conductive agent is used to reduce the electrolyte decomposition side reaction at the interface of the ternary positive electrode material / sulfide solid electrolyte.

[0073] The proportion of the ion-encapsulated composite conductive agent in steps 201 and 202 to the total amount of the ion-encapsulated composite conductive agent can be determined according to actual needs. For example, as an example, the proportion of the ion-encapsulated composite conductive agent in steps 201 and 202 is 50wt%.

[0074] The embodiment of the present application also provides a sulfide all-solid-state battery, which includes a sulfide solid electrolyte, a negative electrode and a positive electrode, wherein the sulfide solid electrolyte is coated on the surface of the positive electrode to form an electrolyte layer, and the negative electrode is covered on the surface of the electrolyte layer.

[0075] The sulfide solid electrolyte can be applied by spraying or painting.

[0076] Further, as an example, the sulfide solid electrolyte includes LGPS, Li3PS4, Li7P3S 11 , Li6PS5Cl or Li8PS5 I.

[0077] Further, as an example, the particle size of the sulfide solid electrolyte is 1 μm-10 μm, and a dense electrolyte layer can be formed by using a smaller electrolyte particle size.

[0078] Furthermore, as an example, the thickness of the electrolyte layer is 20 μm-80 μm. When the thickness is too large, the shuttle efficiency of lithium ions between the positive and negative electrodes becomes low. However, due to the limitations of the uniformity of the electrolyte layer and the process, it is not advisable to make the thickness of the electrolyte layer too small.

[0079] Further, as an example, taking the ternary positive electrode material, binder, ion-coated composite conductive agent and sulfide solid electrolyte as a whole, according to mass fraction, the ternary positive electrode material accounts for 40%-80%, the binder accounts for 0%-10%, the ion-coated composite conductive agent accounts for 2%-15%, and the sulfide solid electrolyte accounts for 10%-50%.

[0080] The present application also provides a method for preparing a sulfide all-solid-state battery, which comprises the following steps:

[0081] 301: Uniformly coating the sulfide solid electrolyte on the outer surface of the composite conductive agent layer to form an electrolyte layer.

[0082] 302: A layer of Li-In alloy is covered on the surface of the electrolyte layer as a negative electrode, and a sulfide all-solid-state battery is obtained by high-voltage packaging.

[0083] The conditions of the high-voltage packaging are: room temperature, 100-500MPa.

[0084] Example 1

[0085] This embodiment provides a VGCF@Li NbO3 ion-coated composite conductive agent.

[0086] In the first step, 0.74 g of Li2CO3 powder and 1.33 g of Nb2O5 powder were mixed and added into a ball mill and milled to mix evenly. The ball milling time was 2 h and the ball milling speed was 300 r / min.

[0087] In the second step, 56.18 g VGCF was added to the mixture obtained in the first step, and a second ball milling was performed. The ball milling time was 2 h and the ball milling speed was 200 r / min.

[0088] In the third step, the mixed powder after the second ball milling is placed in an ark and placed in a tubular furnace for high-temperature sintering. The sintering atmosphere is oxygen. The temperature is increased to 500°C at a heating rate of 5°C / min. After keeping warm for 12 hours, it is naturally cooled to room temperature and the product is collected to obtain a VGCF@Li NbO3 ion-coated composite conductive agent.

[0089] Example 2

[0090] This embodiment provides a VGCF@Li TaO3 ion-coated composite conductive agent.

[0091] In the first step, 0.74 g of Li2CO3 powder and 4.42 g of Ta2O5 powder were mixed and added into a ball mill for uniform mixing. The ball milling time was 4 h and the ball milling speed was 300 r / min.

[0092] In the second step, 89.49 g VGCF was added to the mixture obtained in the first step, and a second ball milling was performed. The ball milling time was 2 h and the ball milling speed was 200 r / min.

[0093] In the third step, the mixed powder after the second ball milling is placed in an ark and placed in a tubular furnace for high-temperature sintering. The sintering atmosphere is oxygen. The temperature is increased to 500°C at a heating rate of 5°C / min. After keeping warm for 12 hours, it is naturally cooled to room temperature and the product is collected to obtain VGCF@Li TaO3 ion-coated composite conductive agent.

[0094] Example 3

[0095] This embodiment provides a LiNi composite conductive agent comprising the composite conductive agent provided in embodiment 1. 0.8 Co 0.1 Mn 0.1 O2 / Li6PS5C l / Li-I n all-solid-state battery.

[0096] In the first step, 6.00 g Li Ni 0.8 Co 0.1 Mn 0.1 O2, 0.50g polytetrafluoroethylene and 0.25g VGCF@LiNbO3 composite conductive agent obtained in Example 1 were uniformly ball-milled and mixed, and the mixed powder was sprayed on the surface of aluminum foil using an electrostatic spraying device to obtain a positive electrode film.

[0097] In the second step, 0.25 g of the VGCF@Li NbO3 composite conductive agent obtained in Example 1 is electrostatically sprayed on the surface of the positive electrode film.

[0098] In the third step, 3.00 g of Li6PS5C1 electrolyte powder is evenly sprayed on the outer surface of the composite conductive agent layer.

[0099] The fourth step is to cover the electrolyte film with a layer of Li-In alloy as the negative electrode material of the battery, and use a solid-state battery mold for static pressurization with a pressure of 200Mpa. Then assemble the battery structure to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 / Li6PS5C l / Li-I n all-solid-state battery.

[0100] Example 4

[0101] This example uses the same preparation method as in Example 3 to obtain LiNi 0.8 Co 0.1 Mn 0.1 The difference between the O2 / Li6PS5C l / Li-In all-solid-state battery is that the mass of the VGCF@Li NbO3 composite conductive agent added in the first and second steps is 0.40g. Specifically:

[0102] In the first step, 6.00 g Li Ni 0.8 Co 0.1 Mn 0.1 O2, 0.50g polytetrafluoroethylene and 0.40g VGCF@LiNbO3 composite conductive agent obtained in Example 1 were uniformly ball-milled and mixed, and the mixed powder was sprayed on the surface of aluminum foil using an electrostatic spraying device to obtain a positive electrode film.

[0103] In the second step, 0.40 g of the VGCF@Li NbO3 composite conductive agent obtained in Example 1 was electrostatically sprayed on the surface of the positive electrode film.

[0104] In the third step, 3.00 g of Li6PS5C1 electrolyte powder is evenly sprayed on the outer surface of the composite conductive agent layer.

[0105] The fourth step is to cover the electrolyte film with a layer of Li-In alloy as the negative electrode material of the battery, and use a solid-state battery mold for static pressurization with a pressure of 200Mpa. Then assemble the battery structure to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 / Li6PS5C l / Li-I n all-solid-state battery.

[0106] Example 5

[0107] This embodiment adopts the same preparation method as that of embodiment 1 to obtain SuperP Li@Li NbO3 ion-coated composite conductive agent, except that 56.18g SuperP Li is used in the second step instead of 56.18g VGCF. Specifically:

[0108] In the first step, 0.74 g of Li2CO3 powder and 1.33 g of Nb2O5 powder were mixed and added into a ball mill and milled to mix evenly. The ball milling time was 2 h and the ball milling speed was 300 r / min.

[0109] In the second step, 56.18 g SuperPL i was added to the mixture obtained in the first step, and a second ball milling was performed. The ball milling time was 2 h and the ball milling speed was 200 r / min.

[0110] In the third step, the mixed powder after the second ball milling is placed in an ark and placed in a tubular furnace for high-temperature sintering. The sintering atmosphere is oxygen. The temperature is increased to 500°C at a heating rate of 5°C / min. After keeping warm for 12 hours, it is naturally cooled to room temperature and the product is collected to obtain the SuperP Li@Li NbO3 ion-coated composite conductive agent.

[0111] Example 6

[0112] This embodiment adopts the same preparation method as that of embodiment 1 to obtain VGCF@Li NbO3 ion-coated composite conductive agent, except that the mass of VGCF added in the second step is 193.04 g. Specifically:

[0113] In the first step, 0.74 g of Li2CO3 powder and 1.33 g of Nb2O5 powder were mixed and added into a ball mill and milled to mix evenly. The ball milling time was 2 h and the ball milling speed was 300 r / min.

[0114] In the second step, 193.04 g VGCF was added to the mixture obtained in the first step, and a second ball milling was performed. The ball milling time was 2 h and the ball milling speed was 200 r / min.

[0115] In the third step, the mixed powder after the second ball milling is placed in an ark and placed in a tubular furnace for high-temperature sintering. The sintering atmosphere is oxygen. The temperature is increased to 500°C at a heating rate of 5°C / min. After keeping warm for 12 hours, it is naturally cooled to room temperature and the product is collected to obtain a VGCF@Li NbO3 ion-coated composite conductive agent.

[0116] Example 7

[0117] This embodiment adopts the same preparation method as that of Embodiment 1 to obtain VGCF@Li NbO3 ion-coated composite conductive agent, except that the mass of VGCF added in the second step is 11.84 g.

[0118] Specifically:

[0119] In the first step, 0.74 g of Li2CO3 powder and 1.33 g of Nb2O5 powder were mixed and added into a ball mill and milled to mix evenly. The ball milling time was 2 h and the ball milling speed was 300 r / min.

[0120] In the second step, 11.84 g of VGCF was added to the mixture obtained in the first step, and a second ball milling was performed. The ball milling time was 2 h and the ball milling speed was 200 r / min.

[0121] In the third step, the mixed powder after the second ball milling is placed in an ark and placed in a tubular furnace for high-temperature sintering. The sintering atmosphere is oxygen. The temperature is increased to 500°C at a heating rate of 5°C / min. After keeping warm for 12 hours, it is naturally cooled to room temperature and the product is collected to obtain a VGCF@Li NbO3 ion-coated composite conductive agent.

[0122] Example 8

[0123] This example adopts the same preparation method as that of Example 3 to obtain a Li MnO4 / Li6PS5C l / Li-In all-solid-state battery, except that 6.00 g Li MnO4 is used instead of 6.00 g Li Ni in the first step. 0.8 Co 0.1 Mn 0.1 O2. Specifically:

[0124] In the first step, 6.00 g of Li MnO4, 0.50 g of polytetrafluoroethylene and 0.25 g of the VGCF@Li NbO3 composite conductive agent obtained in Example 1 were uniformly ball-milled and mixed, and the mixed powder was sprayed on the surface of the aluminum foil using an electrostatic spraying device to obtain a positive electrode film.

[0125] In the second step, 0.25 g of the VGCF@Li NbO3 composite conductive agent obtained in Example 1 is electrostatically sprayed on the surface of the positive electrode film.

[0126] In the third step, 3.00 g of Li6PS5C1 electrolyte powder is evenly sprayed on the outer surface of the composite conductive agent layer.

[0127] The fourth step is to cover the electrolyte film with a layer of Li-In alloy as the negative electrode material of the battery, and use a solid-state battery mold for static pressurization with a pressure of 200 MPa. Then assemble the battery structural parts to obtain the Li MnO4 / Li6PS5Cl / Li-In all-solid-state battery.

[0128] Example 9

[0129] This example uses the same preparation method as in Example 3 to obtain LiNi 0.8 Co 0.1 Mn 0.1 The difference between the O2 / Li6PS5C l / Li-I n all-solid-state battery is that the conductive agent used is VGCF conductive agent without ion coating layer.

[0130] Example 10

[0131] This example uses the same preparation method as in Example 3 to obtain LiNi 0.8 Co 0.1 Mn 0.1 O 2 / The difference between the Li6PS5C l / Li-In all-solid-state battery and the Li6PS5C l / Li-In all-solid-state battery is that no conductive agent products are used, and only 0.50g Li NbO3 is used to replace 0.50g VGCF@Li NbO3 composite conductive agent.

[0132] Embodiment 11

[0133] This embodiment adopts the same preparation method as that of Embodiment 1 to obtain a VGCF@Li NbO3 ion-coated composite conductive agent, except that the sintering conditions are: heating to 700°C at a heating rate of 5°C / min, keeping the temperature constant for 12 hours, and then naturally cooling to room temperature.

[0134] Example 12

[0135] This embodiment adopts the same preparation method as that of Embodiment 1 to obtain a VGCF@Li NbO3 ion-coated composite conductive agent, except that the sintering conditions are: heating to 250°C at a heating rate of 5°C / min, keeping the temperature constant for 12 hours, and then naturally cooling to room temperature.

[0136] The four-probe method is used to test the electrode resistivity of the conductive agent powder; the DC internal resistance tester is used to test the AC internal resistance of the solid-state battery; and the electrochemical workstation cycle test method is used to test the cycle performance of the solid-state battery.

[0137] Conductive agent film resistivity test method: Li Ni 0.8 Co 0.1 Mn 0.1 O2, polytetrafluoroethylene and conductive agent powder were mixed in a mass ratio of 90:5:5 and coated on the surface of the PET film using a 200μm scraper. The volume resistivity of the electrode was tested using a four-probe electrode resistance meter with a test pressure of 25Mpa and a holding time of 15s.

[0138] Powder resistivity test method: Take 2.00g sample and put it on the sample stage of powder resistivity tester, apply a pressure of 90MPa, and maintain the pressure for 10s.

[0139] DC internal resistance test method: the working voltage is 5.0V, each group of embodiments is tested three times in parallel, and the average value of the data is taken as the final test result.

[0140] Battery cycle performance test method: the charge and discharge window is 2.5V-4.5V, the current density is 1C, the number of cycles is 100, and the capacity retention rate after 100 cycles is used to indicate the quality of the cycle performance.

[0141] Table 1 Film resistivity of composite conductive agent

[0142] Resistivity (Ω·cm) Example 1 15.86 Example 2 17.21 Example 5 15.98 Example 6 22.54 Example 7 20.76 Embodiment 11 23.27 Example 12 21.79

[0143] From the comparative data in Table 1, since the ion-conductive coating layer contains a large amount of lithium ions, a large amount of lithium ions can improve the polarization effect brought by the space charge layer at the electrolyte / positive electrode material interface, improve the lithium ion transmission capacity at the interface, and increase the lithium ion transmission flux. Therefore, the resistivity of Example 1, Example 2, Example 5, Example 6 and Example 7 is relatively low, and the resistance is relatively small.

[0144] In Example 11, since the annealing temperature is 700°C, the high temperature causes the lattice atoms to move violently, the crystal structure of the ionic coating layer changes, and the ion transmission efficiency decreases, so the resistivity increases and the resistance increases. It can be seen that too high an annealing temperature will reduce the lithium ion transmission flux.

[0145] Similarly, in Example 12, since the annealing temperature is 250°C, the temperature is too low to grow a uniformly coated Li NbO3 coating layer on the surface of the conductive agent matrix, and the transmission of lithium ions is restricted here. A space charge layer may also be generated at the interface between the conductive agent matrix and the electrolyte, increasing the polarization of the battery. It can be seen that the annealing temperature is too low to achieve the effect of improving the lithium ion transmission capacity at the interface.

[0146] Table 2 Comparison of battery cycle performance

[0147] Internal resistance(Ω) 100-cycle capacity retention rate Example 3 1.77 80.23% Example 4 1.59 82.12% Example 8 2.31 75.23% Example 9 5.24 48.68% Example 10 12.88 19.27%

[0148] Combination Figure 3 From the data in Table 2, it can be seen that the internal resistance of Examples 3, 4 and 8 is much lower than that of Examples 9 and 10, indicating that the lithium ions of Examples 3, 4 and 8 have a very high transmission flux, which is beneficial to the battery cycle performance and rate performance. From the perspective of improving the capacity retention rate after 100 cycles, more than 80% is obtained, which also confirms that the present application can indeed improve the battery cycle performance and rate performance.

[0149] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. An ion-coated composite conductive agent, characterized in that: It comprises a conductive agent matrix and an ion-conductive coating layer for increasing the lithium ion transmission flux, wherein the ion-conductive coating layer is coated on the outer wall surface of the conductive agent matrix and comprises lithium ions.

2. The ion-encapsulated composite conductive agent according to claim 1, characterized in that: The ion-conducting coating layer also includes oxygen ions.

3. The ion-encapsulated composite conductive agent according to claim 1, characterized in that: The ion-conducting coating layer includes lithium niobate LiNbO3, lithium titanate Li4Ti5O 12 , lithium tantalate LiTaO3 or more.

4. The ion-encapsulated composite conductive agent according to claim 1, characterized in that: The mass ratio of the ion-conducting coating layer to the mass ratio of the ion-coated composite conductive agent is 1%-20%.

5. The ion-encapsulated composite conductive agent according to claim 1, characterized in that: The conductive agent matrix includes one or more of conductive carbon black CB, vapor-grown carbon fiber VGCF, SuperPLi, conductive graphite and carbon nanotube CNT.

6. A method for preparing the ion-encapsulated composite conductive agent according to claim 1, characterized in that: It includes: The raw material of the ion-conducting coating layer and the conductive agent matrix are ball-milled to obtain a mixed powder, wherein the raw material of the ion-conducting coating layer includes a lithium source and a metal oxide; The mixed powder is annealed to obtain an ion-coated composite conductive agent.

7. The method for preparing the ion-encapsulated composite conductive agent according to claim 6, characterized in that: The lithium source includes one or more of lithium carbonate Li2CO3, lithium oxide Li2O, lithium sulfate Li2SO4, lithium nitrate LiNO3 and lithium hydroxide LiOH.

8. The method for preparing the ion-encapsulated composite conductive agent according to claim 6, characterized in that: The metal oxide includes one or more of niobium pentoxide Nb2O5, titanium dioxide TiO2, and tantalum pentoxide Ta2O5.

9. The method for preparing the ion-encapsulated composite conductive agent according to claim 6, characterized in that: The molar proportion of the metal oxide in the raw material of the ion-conducting coating layer is 40%-60%.

10. The method for preparing the ion-encapsulated composite conductive agent according to claim 6, characterized in that: The mass fraction of the conductive agent matrix in the mixed powder is 90%-97%.

11. The method for preparing the ion-encapsulated composite conductive agent according to claim 6, characterized in that: The annealing treatment includes: the ambient atmosphere is oxygen, the annealing temperature is 350° C.-600° C., and the annealing time is 10-15 hours.

12. A positive electrode, characterized in that: The invention comprises a ternary positive electrode material, a binder, a positive electrode current collector, and an ion-encapsulated composite conductive agent as claimed in any one of claims 1 to 5.

13. The positive electrode according to claim 12, characterized in that: The ternary positive electrode material includes LiCoO2, Li(Ni a Co b X c )O2 or LiMn2O4, wherein a+b+c=1, X=Mn or Al.

14. The positive electrode according to claim 12, characterized in that: The particle size of the ternary positive electrode material is 500nm-100μm.

15. The positive electrode according to claim 12, characterized in that: The binder includes one or more of polythiophene, polypyrrole, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polystyrene, polyacrylamide, and ethylene-propylene-diene copolymer resin.

16. The positive electrode according to claim 12, characterized in that: The positive electrode current collector includes one or more of aluminum foil, carbon-coated aluminum foil or composite aluminum foil.

17. A method for preparing a positive electrode according to any one of claims 12 to 16, characterized in that: It includes: The ternary positive electrode material, the binder and a part of the ion-coated composite conductive agent are uniformly mixed and then sprayed on the surface of the positive electrode current collector to form a positive electrode film; The remaining ion-coated composite conductive agent is coated on the surface of the positive electrode film to form a composite conductive agent layer to obtain a positive electrode.

18. A sulfide all-solid-state battery, characterized in that: It comprises a sulfide solid electrolyte, a negative electrode and a positive electrode as claimed in any one of claims 12 to 16, wherein the sulfide solid electrolyte is coated on the surface of the positive electrode to form an electrolyte layer, and the negative electrode is covered on the surface of the electrolyte layer.

19. The sulfide all-solid-state battery according to claim 18, characterized in that: The sulfide solid electrolyte includes LGPS, Li3PS4, Li7P3S 11 , Li6PS5Cl or Li8PS5 I.

20. The sulfide all-solid-state battery according to claim 18, characterized in that: The particle size of the sulfide solid electrolyte is 1 μm-10 μm.

21. The sulfide all-solid-state battery according to claim 18, characterized in that: The thickness of the electrolyte layer is 20 μm-80 μm.

22. The sulfide all-solid-state battery according to claim 18, characterized in that: Taking the ternary positive electrode material, binder, ion-coated composite conductive agent and sulfide solid electrolyte as a whole, according to mass fraction, the ternary positive electrode material accounts for 40%-80%, the binder accounts for 0%-10%, the ion-coated composite conductive agent accounts for 2%-15%, and the sulfide solid electrolyte accounts for 10%-50%.

Citation Information

Patent Citations

  • Conductive agent, preparation method thereof and secondary battery

    CN114520330A

  • Conductive agent and preparation method thereof, preparation method of positive plate and preparation method of solid-state battery

    CN115642253A